Effect of the Major Micronutrients on Quantity and Quality Traits of Broccoli under the Kanpur Region (Brassica oleracea var. Italica L.) - , Shubham Singh; , Vinay Joseph Silas; , Jitendra Kumar; , Raghvendra Singh; , Alok Kumar (Archives of Current Research International, 2025)
A field experiment was conducted during Rabi 2024 at the Horticulture Research Farm, Faculty of Agricultural Sciences and Allied Industries, Rama University, Kanpur (U.P.). The experiment was laid out in a Randomized Block Design (RBD) with nine treatments, each replicated three times, based on a one-year trial. The treatments are T1 (Control) T2 Zinc (3kg/ha) T3 Mo (1.5 kg/ha) T4 Mn (2 kg/ha) T5 Boron (2.5-3 kg) T6 (B+Mo) T7 (B+Mn+Zinc) T8 (Mo+Mn) T9 (B+Mo+Mn+Zinc). Each unit plot measured 4.5 m², with a plant spacing of 60 cm × 45 cm, accommodating a total of 10 plants per plot. The treatments were randomly assigned to plots in each replication. The results revealed that the application of T9 (B + Mo + Mn + Zn) recorded the highest plant growth, yield, and quality attributes of broccoli, significantly outperforming the other treatments. In contrast, the control (T1) recorded the lowest values for growth, yield, and quality parameters. In terms of economics, T9 also recorded the highest gross return, net return (Rs. ha⁻¹), and benefit-cost ratio, indicating its economic viability over other treatments.